Proposta de atividades para o ensino da matemática financeira - Lopes, Murilo Cesar (Universidade Federal de São Carlos, 2022)
This work presents some activities on financial mathematics. The activities were developed with three groups of students of high school in a public school and it were based on real data, which help students to have a sustainable consumption and a responsible financial life. Also, were presented some basics concepts about financial investments.
Proposal of activities for the teaching of financial mathematics
Keywords: Sistemas de amortização; Ensino de matemática; Matemática financeira; Amortization methods; Mathematics teaching; Financial mathematics; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM